Exploring the Genetic Diversity of Isolated Hypogonadotropic Hypogonadism and Its Phenotypic Spectrum: A Case Series - VSR Danda; SR Paidipelly; M Verepula; P Lodha; KR Thaduri; C Konda; A Ruhi (JRI, 2021)
Background: Isolated hypogonadotropic hypogonadism (IHH) is a rare disorder being classified as Kallmann syndrome (KS). The present study was conducted to study the genotype and relative proportion of different genetic mutations in IHH and to assess its correlation with phenotype. Methods: Eleven consecutive subjects presenting to the Department of Endocrinology were retrospectively analyzed during May 2017 to December 2018 with IHH. Phenotypic features and hormonal studies were analyzed along with clinical exome by targeted gene sequencing (Next generation sequencing). Thirty-nine relevant genes were tested in the analysis. Results: Of the 11 patients studied, five had KS and six had nIHH. At diagnosis, mean chronological age was 25 years. There were associated anomalies in KS group including bimanual synkinesia (n=2), unilateral renal agenesis (n=1) and submucosal cleft palate (n=1). Absence or hypoplasia of the olfactory bulb/sulci was found in 4/5 patients with KS. Genetic mutations in KAL1, CHD7, FGFR1, GNRHR, PROKR2, HS6ST1 genes were found in nine of the eleven subjects. Of the five subjects with KS, two had mutations in KAL1 gene. Two siblings who had bimanual synkinesia had CHD7 mutation. The genotype of nIHH subjects (n=6) was more heterogeneous. Conclusion: This study analyzed the clinical, endocrinological, and genetic features in IHH patients. Detectable genetic mutations were seen in a large proportion of cases. A considerable heterogeneity was seen in the genotype with new variants detected. A definite correlation of phenotype-genotype was not possible, and significant overlap was seen between CHD7 and KAl1, and FGFR1 phenotypes.